2022
DOI: 10.1097/mao.0000000000003574
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implant Outcomes in Patients With Otosclerosis: A Systematic Review

Abstract: ObjectiveThis study aimed to establish hearing outcomes after cochlear implantation in patients with otosclerosis.Materials and MethodsWe conducted a systematic review and narrative synthesis. Databases searched were as follows: MEDLINE, PubMed, Embase, Web of Science, Cochrane Collection, and ClinicalTrials.gov. No limits were placed on language or year of publication. The review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement.ResultsSearches i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…In case of refractory FNS, surgical removal of the CI may be necessary (Smullen et al 2005, Sefien andHamada 2019). Although a previous systematic review and meta-analysis reported a low overall FNS rate of around 5% (Van Horn et al 2020), some subjects exhibit a higher risk of developing this condition depending on the underlying cochlear pathology and anatomy; for instance, otosclerosis may modify the density and therefore the resistivity of the bone tissue, which affect the magnitude and extent of EF patterns through the cochlea and nearby tissue structures (Vanpoucke et al 2004, Seyyedi et al 2013, Burmeister et al 2017, Burck et al 2022, Lam et al 2022. In addition to MP, other stimulation modes, such as bipolar (BP), tripolar (TP), and partial TP (pTP), which aim to improve the focality of the EF over the targeted auditory nerve fibres by reducing current spread, have also been suggested to help alleviate FNS (van der Westhuizen et al 2022, Eitutis et al 2022a.…”
Section: Introductionmentioning
confidence: 99%
“…In case of refractory FNS, surgical removal of the CI may be necessary (Smullen et al 2005, Sefien andHamada 2019). Although a previous systematic review and meta-analysis reported a low overall FNS rate of around 5% (Van Horn et al 2020), some subjects exhibit a higher risk of developing this condition depending on the underlying cochlear pathology and anatomy; for instance, otosclerosis may modify the density and therefore the resistivity of the bone tissue, which affect the magnitude and extent of EF patterns through the cochlea and nearby tissue structures (Vanpoucke et al 2004, Seyyedi et al 2013, Burmeister et al 2017, Burck et al 2022, Lam et al 2022. In addition to MP, other stimulation modes, such as bipolar (BP), tripolar (TP), and partial TP (pTP), which aim to improve the focality of the EF over the targeted auditory nerve fibres by reducing current spread, have also been suggested to help alleviate FNS (van der Westhuizen et al 2022, Eitutis et al 2022a.…”
Section: Introductionmentioning
confidence: 99%